2016
DOI: 10.1080/02670836.2016.1201927
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stacking fault energy in electrically assisted uniaxial tension of FCC metals

Abstract: Electrically assisted manufacturing is based on the electro-plastic effect induced by electricity on the material flow during deformation and represents an alternative method for forming materials. Several studies have pointed out the real effectiveness of this technique, but no relations among microstructure, electrical resistivity, crystal structure and deformation-mode have been revealed. In the present work, the stacking fault energy (SFE) was taken into account and three FCC materials possessing different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In a previously published work, a SFE dependence of EPE on the total elongation has been observed [32]. High SFE materials show a better formability compared to the low SFE ones.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In a previously published work, a SFE dependence of EPE on the total elongation has been observed [32]. High SFE materials show a better formability compared to the low SFE ones.…”
Section: Discussionmentioning
confidence: 82%
“…Magargee demonstrated that each material has a different current density sensitivity for EPE to occur, which depends on the resistivity of the material (the higher the resistivity, the lower the threshold) [31]. A dependence from the Stacking Fault Energy (SFE) on the occurrence of the EPE has also been observed [32]. An interesting theory was proposed by Ruszkiewicz et al [33]: stagnation of electrons in the proximity of obstacles increases the electron to atom ratio, decreasing the bond energy and eventually easing the breaking and reforming of metallic bonds favoring plastic deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The electroplastic effect has shown to improve the formability on a wide variety of metallic materials such as aluminum [15][16][17], titanium [18][19][20], magnesium [21][22][23], stainless steels [24,25] and on a variety of forming processes as well. Some of the authors observed a relationship of the onset of EPE on FCC materials with respect the stacking fault energy (SFE), which drives dislocation's motion within the material [26]. Conversely to EAM, during electropulsing treatments (EPTs), electrical current is applied prior or after deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Electroplastic effect has shown to improve the formability on a wide variety of metallic materials such as aluminum [15][16][17], titanium [18][19][20], magnesium [21][22][23], stainless steels [24,25] and on a variety of forming process as well. Some of the authors observed a relation of the onset of EPE on FCC materials depending on the SFE, which drives dislocation's motion within the material [26]. Conversely to EAM, during electropulsing heat treatments (EPTs), electrical current is applied prior or after deformation.…”
Section: Introductionmentioning
confidence: 99%